The all-encompassing eye of Ukraine : Ivan Nechui-Levytsʹkyiʹs realist prose - Tarnawsky, Maxim (University of Toronto Press, 2015)
In The All-Encompassing Eye of Ukraine, Maxim Tarnawsky presents a thorough and much-needed reexamination of Ukrainian novelist Ivan Nechui-Levyts'kyi and his work.